Alcohol and Australian veterans : a resource for improving pathways for care - Pead, John.; Australia. Department of Veterans' Affairs; Australian Centre for Posttraumatic Mental Health (Canberra : Dept. of Veterans' Affairs, 2006)
" ... arises from a conference in 2001 conducted as a joint initiative by the Department of Veterans Affairs (DVA) and the Australian Centre for Posttraumatic Mental Health (ACPMH) ... aims to ensure that the programs and partnerships are in place to address alcohol problems in the veteran community in a way that is integrated with the management of other physical and mental health issues; a way that is focussed on the needs of individual veterans and their families, rather than the needs and structures of the service system"--Introd.
"Publication no. P01335"--T.p. verso.
At foot of title: The right mix, your health & alcohol.
Includes bibliographical references.
Keywords: Veterans -- Alcohol use -- Australia -- Congresses; Alcoholism -- Treatment -- Australia -- Congresses; Alcoholism -- Australia -- Prevention -- Congresses; Post-traumatic stress disorder -- Treatment -- Australia -- Congresses